IMMUNOMODULATORY THERAPY OF CHRONIC RECURRENT CYSTITIS IN WOMEN - O. S. Streltsov; V. N. Krupin (Вестник урологии, 2014)
The role ofimmunomodulatory therapy to stimulate bactericidal properties humoral defensecells of neutrophilsin patients suffering fromrecurrent bladder infection. Found that the inclusion ofthe immunomodulatorin the treatment regimen of exacerbations of chronic cystitis contributes to increasing the activation of phagocytic index of neutrophils and reserve leads to a significant decrease in the frequency of exacerbations of the disease after basic andpreventive courses of treatment.